(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
The article analyses EU Directives 2022/2464 (CSRD) and 2024/1760 (CS3D) with regard to the climate-planning obligations imposed on large companies. These obligations reflect the emergence of businesses as private powers horizontally involved in climate governance, through science-based transition plans. The contribution explores the legal nature of these plans, their role as instruments for the co-design of climate policies, and the different enforcement models, by comparing the French system shaped by the Loi de Vigilance with the Italian one, which lacks comparable legislation, while also taking into account – in a forward-looking perspective – the potential impact of the proposed Omnibus Directive.